Masyarakat sivil dan pendemokrasian: perbincangan konseptual (Civil society and democratization in Malaysia: a conceptual analysis) - Md. Salleh Md. Said,; Mohammad Agus Yusoff,; Leo Agustino,; Jayum Jawan, (Penerbit UKM, 2011)
This article conceptually analyses the relationship between civil society and democratization process. This discussion is important for two reasons; firstly, democratization in many countries is oftenly being initiated by civil society movements seeking for political changes. It has been the role of civil society that has opened up demand for more social-political freedom. Hence, a question is raised in this article, what do we meant by civil society? How is it formed? Secondly, what is the relationship between civil society and the process of democratization? What are factors that have driven and shaped democratization process? The article argues that civil society is a vital factor in democratization process in many non-democratic countries either in Eastern Europe, South America or Asia. It can be argued that civil society has the ability to deal with repressive, hegemonic and dominative government actions against the people. Finally, this article also argues that civil society plays a crucial role in preventing tyranny and act as advocators, intermediaries, opposition and supporters who fought hard in promoting and fosteing democracy in their respective countries.